Encyclopedia of communities of practice in information and knowledge management - Coakes, Elayne, 1950-; Clarke, Steve, 1950- (Idea Group Reference, 2006)
"This encyclopedia will give readers insight on how other organizations have tackled the necessary means of sharing knowledge across communities and functions"--Provided by publisher.